Matematyka
 
Brak innych książek z tego przedmiotu
 
Autorzy: Drążek Anna, Duvnjak Ewa, Kokiernak-Jurkiewicz Ewa
Wydawnictwo: WSiP
Rok wydania: 2016
Oblicz. 3√28-0,5³√448+5√63+³√56-4√175 4.5 gwiazdek na podstawie 6 opinii

`=3*2*sqrt(7)-0,5*root3(64)*root(3)(7)+5*3*sqrt(7)+2*root(3)(7)-4*5*sqrt(7)=`

`=6sqrt(7)-0,5*4*root(3)(7)+15sqrt(7)+2root(3)(7)-20sqrt(7)=sqrt(7)-2root(3)(7)+2root(3)(7)=sqrt(7)`

`b) \ \ \ 1 1/4root(3)(0,04)+0,25root(3)(5)-5root(3)(0,32)+1/2root(3)(135)=`   `5/4*root(3)(0,008*5)+25/100*root(3)(5)-5root(3)(0,064*5)+1/2*root(3)(27*5)=`

`=5/4*root(3)(0,008)*root(3)(5)+1/4*root(3)(5)-5*root(3)(0,064)*root(3)(5)+1/2*root(3)(27)*root(3)(5)=5/4*0,2*root(3)(5)+1/4*root(3)(5)-5*0,4*root(3)(5)+1/2*3*root(3)(5)=`

`=5/4*2/10*root(3)(5)+1/4*root(3)(5)-2*root(3)(5)+3/2*root(3)(5)=1/4*root(3)(5)+1/4*root(3)(5)-2*root(3)(5)+3/2*root(3)(5)=2/4*root(3)(5)-2*root(3)(5)+3/2*root(3)(5)=`

`=1/2*root(3)(5)-2*root(3)(5)+3/2*root(3)(5)=2root(3)(5)-2root(3)(5)=0`

`c) \ \ \ 4sqrt(0,12)-0,3sqrt(3)+3sqrt(18,75)-10sqrt(0,27)=4sqrt(0,04*3)-0,3sqrt(3)+3sqrt(6,25*3)-10sqrt(0,09*3)=`

`=4sqrt(0,04)*sqrt(3)-0,3sqrt(3)+3sqrt(6,25)*sqrt(3)-10sqrt(0,09)*sqrt(3)=4*0,2sqrt(3)-0,3sqrt(3)+3*2,5sqrt(3)-10*0,3sqrt(3)=`

`=0,8sqrt(3)-0,3sqrt(3)+7,5sqrt(3)-3sqrt(3)=5sqrt(3)`